A methodological study to determine emotional and behavioural problems with associated factors among children of institutional homes in Raipur, Chhattisgarh - Agrawal, Akshat; Sinha, Ashish; Gupta, Shubhangi; Kotwani, Pranshul (International Journal Of Community Medicine And Public Health, 2022)
Background: Children residing in institutional homes are more susceptible to behavioural and emotional problems in comparing to other children in the same age group. It has been discovered that when developmental processes inside the institution are accelerated over time, they can result in restricted cognitive activity and cultural expression patterns. Unresolved negative emotions, such as anger and depression, put children at danger of growing up with harmful emotions. Methods: To study the children's behavioural and emotional problems, in the present study, the sample of 142 people who lived in Raipur's institutional homes were considered. A semi-structured questionnaire was used to obtain sociodemographic information. The behavioural and emotional difficulties in them were assessed using the strengths and difficulties questionnaire (SDQ) with impact supplement. The sex of the children, satisfaction with the food provided, caretaker behaviour, years of stay, and reasons for being at the institution were not shown to be substantially associated with emotional and behavioural difficulties in children in our study. Results: Based on the SDQ, 52.1% children and adolescents in the present study had scores greater than the cut-off score of 28, indicating that those with SDQ scores greater than 28 had some social and behavioural problems, and hence are marked positive for emotional and behavioural problems. The age of the participants was found to be a strong predictor of emotional and behavioural issues. Conclusions: The majority of the subjects were pleased with their caretakers' behaviour, the quality of the water supply, and the sanitary facilities, implying favourable environmental conditions.